Effects of sodium tanshinone IIA sulfonate injection on inflammatory factors and vascular endothelial function in patients with acute coronary syndrome undergoing percutaneous coronary intervention: A systematic review and meta-analysis of randomized clinical trials - Kan, Zunqi; Yan, Wenli; Yang, Mengqi; Gao, Huanyu; Meng, Dan; Wang, Ning; Fang, Yuqing; Wu, Lingyu; Song, Yongmei (Frontiers in Pharmacology, 2023)
Background: Patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) therapy may experience further damage to the vascular endothelium, leading to increased inflammatory response and in-stent thrombosis. In many clinical studies, sodium tanshinone IIA sulfonate injection (STS) has been found to reduce inflammatory factors and enhance vascular endothelial function in patients with ACS while improving the prognosis of PCI. However, to date, there has been no systematic review assessing the effectiveness and safety of STS on inflammatory factors and vascular endothelial function. Purpose: The aim of this study is to systematically review the effects of STS on inflammatory factors and endothelial function in patients with ACS treated with PCI. Methods: Until October 2022, eight literature databases and two clinical trial registries were searched for randomized controlled trials (RCTs) investigating STS treatment for ACS patients undergoing PCI. The quality of the included studies was assessed using the Cochrane Risk Assessment Tool 2.0. Meta-analysis was performed using RevMan 5.4 software. Results: Seventeen trials met the eligibility criteria, including 1,802 ACS patients undergoing PCI. The meta-analysis showed that STS significantly reduced high-sensitivity C-reactive protein (hs-CRP) levels (mean difference [MD]=-2.35, 95% CI [-3.84, -0.86], P=0.002), tumor necrosis factor-alpha (TNF-α) levels (standard mean difference [SMD]=-3.29, 95%CI [-5.15, -1.42], P=0006), matrix metalloproteinase-9 (MMP-9) levels (MD=-16.24, 95%CI [-17.24, -15.24], P<0.00001), and lipid peroxidation (LPO) levels (MD=-2.32, 95%CI [-2.70, -1.93], P<0.00001), and increased superoxide dismutase (SOD) levels (SMD=1.46, 95%CI [0.43, 2.49], P=0006) in patients with ACS. In addition, STS significantly decreased the incidence of major adverse cardiovascular events (relative risk=0.54, 95%CI [0.44, 0.66], P<0.00001). The quality of evidence for the outcomes was assessed to be very low to medium. Conclusion: STS can safely and effectively reduce the levels of hs-CRP, TNF-α, MMP-9, and LPO and increase the level of SOD in patients with ACS treated with PCI. It can also reduce the incidence of adverse cardiovascular events. However, these findings require careful consideration due to the small number of included studies, high risk of bias, and low to moderate evidence. In the future, more large-scale and high-quality RCTs will be needed as evidence in clinical practice.